Shared manufacturing: opportunities and prospects - Elkanah Olaosebikan Oyetunji; Oriyomi Idris Abagun; Ebenezer Ayooluwa Oyetunji (Journal of Applied Research in Technology & Engineering)
Shared manufacturing (SharedMfg) is a new mode of social manufacturing that is gaining massive attention globally as it incorporates the concept of sharing economy into smart manufacturing systems and is centered on maximizing the utility of things and services. It extends the scope and depth of resource sharing and enables society-based manufacturing integration. It not only helps to achieve full sharing of large-scale manufacturing resources and capabilities but also benefits economic income and reduces the manufacturing costs in small and medium-sized enterprises. Being a friendly-sharing concept, the SharedMfg concept spans across all stages of manufacturing and thus increases the sociality of manufacturing, thereby benefiting both the resource providers and consumers with improved capabilities and competitiveness. However, with the concept in its infancy stage, there is little clarification on its benefits.  While few companies in most developed countries have started reaping these benefits through collaboration with their peers, most of the firms worldwide are still hesitant and resistant to adopting the concept. Therefore, this paper aims to elucidate the potential benefits of the innovative concept. These opportunities were classified into six major categories, and each category was analyzed meticulously. It was then concluded that manufacturing companies around the world need to be encouraged to embrace the SharedMfg concept. The ubiquitous implementation of this manufacturing mode will not only benefit the participating firms but also serve the economy and foster sustainable manufacturing and development.